Group B streptococcal bacteraemia: changing trends in a tropical region of Australia. Issue 5 (10th May 2022) - Alizzi, Mohammed; Rathnayake, Romesh; Sivabalan, Pirathaban; Emeto, Theophilus I.; Norton, Robert
Abstract: Background: Group B streptococcus (GBS) is a recognised perinatal and neonatal pathogen. There are reports of increasing GBS sepsis globally outside this demographic. North Queensland is part of tropical Australia, with a relatively high proportion of Indigenous Australians. Aims: To analyse the epidemiology of GBS bacteraemia and explore associated risk factors. Methods: This was a 10‐year retrospective review of GBS bacteraemia in a tertiary facility in North Queensland, between 2010 and February 2020. Data variables collected included: demographics, risk factors, clinical source and outcomes. Multivariable logistic regression was performed to examine the association of indigenous status and other relevant clinical factors with mortality from GBS bacteraemia at 3 months. Results: Of the 164 total cases, 123 were not pregnancy related. The annual rate of GBS bacteraemia for the indigenous population was 12.48 per 100 000 and 4.84 per 100 000 for the non‐indigenous population. Indigenous patients were more likely to have diabetes and chronic kidney disease compared with the non‐indigenous patients. Males (adjusted odds ratio (AOR) = 4.34; 95% CI 1.14−16.56; P = 0.031) and immunosuppressed patients (AOR = 11.49; 95% CI 2.73−48.42; P < 0.001) were more likely to experience mortality at 3 months from GBS bacteraemia even after adjusting for other risk factors respectively. Conclusion: GBS bacteraemia is deviating from being primarily a neonatal disease. While the indigenous population of North Queensland are disproportionately affected, the demographics affected differ. GBS appears to target the older non‐indigenous patients with greater comorbidities. In the non‐indigenous population, invasive GBS disease is an emerging issue. Three‐month mortality appears to be increased in males and the immunosuppressed.